Security culture as a factor in preventing victimization of information technology users - Stajić Ljubomir; Radivojević Nenad (Temida)
Development in the field of information technologies in the last few decades has led to significant changes in the daily lives of citizens, the functioning of the economy, government bodies and society as a whole. Information technologies have enabled unimaginable possibilities in terms of social development. However, this field is not immune to increasingly numerous dangerous intentional or unintentional abuses. This imposes the need to raise awareness, knowledge and skills to protect yourself and others in this field. The security culture as a concept that integrates issues of solving the problem of endangering information security plays a significant role in this. The subject of this paper is the analysis of the connection between security culture and information technologies, as a cultural asset of modern society, especially the security culture of information technology users. The paper aims to establish a theoretical framework on the role and importance of security culture. Also, the aim is to give a set of “golden” rules of security culture in information technologies, the adoption of which will increase the possibility of preventing victimization of information technology users.